Proviral sequences that restrict retroviral expression in mouse embryonal carcinoma cells. - Loh, T P (1987)
Embryonal carcinoma (EC) cells are nonpermissive for retrovirus replication. Restriction of retroviral expression in EC cells was studied by using DNA transfection techniques. To investigate the activity of the Moloney murine leukemia virus (M-MuLV)enhancer and promoter sequences, the M-MuLV long terminal repeat and the defined long terminal repeat deletions were linked to neo structural gene sequences that encode resistance to the neomycin analog G418. Transient expression data and drug resistance frequencies support the findings that the M-MuLV enhancer is not active in EC cells but that promoter sequences are functional. In addition, a proviral DNA fragment that encodes the leader RNA sequence of a M-MuLV recombinant retrovirus was found to restrict expression specifically in EC cells. Deletion analysis of the leader fragment localized the inhibitory sequences to a region that spans the M-MuLV tRNA primer binding site. It is not known whether restriction occurs at a transcriptional or posttranscriptional level, but steady-state RNA levels in transient expression assays were significantly reduced.